2015
DOI: 10.5704/moj.1511.019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nerve Exploration in Supracondylar Humerus Fracture in Children with Nerve Injury

Abstract: The supracondylar humerus fracture (SCHF) in children is common and can be complicated with nerve injury either primarily immediate post-trauma or secondarily posttreatment. The concept of neurapraxic nerve injury makes most surgeons choose to ‘watch and see’ the nerve recovery before deciding second surgery if the nerve does not recover. We report three cases of nerve injury in SCHF, all of which underwent nerve exploration for different reasons. Early reduction in the Casualty is important to release the ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Both the studies showed no significant improvement in nerve complications. It should also be borne in mind that the documented incidence of primary nerve injury in these fractures is 7-10% and up to 6% for secondary nerve injury and the indication for intervention in these two distinct nerve injury pattern is different (3).…”
Section: Original Paper Původní Prácementioning
confidence: 99%
“…Both the studies showed no significant improvement in nerve complications. It should also be borne in mind that the documented incidence of primary nerve injury in these fractures is 7-10% and up to 6% for secondary nerve injury and the indication for intervention in these two distinct nerve injury pattern is different (3).…”
Section: Original Paper Původní Prácementioning
confidence: 99%